2018
DOI: 10.1101/255943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic detection of amino acid substitutions in proteome reveals a mechanistic basis of ribosome errors

Abstract: Translation errors limit the accuracy of information transmission from DNA to proteins. Selective pressures shape the way cells produce their proteins: the translation machinery and the mRNA sequences it decodes co-evolved to ensure that translation proceeds fast and accurately in a wide range of environmental conditions. Our understanding of the causes of amino acid misincorporations and of their effect on the evolution of protein sequences is largely hindered by the lack of experimental methods to observe er… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In yeast, bacterial [19], and mammalian [9] cells, faster elongation rates compromise the accuracy of codon:anticodon recognition, although it has recently been reported that rates of translation elongation do not correlate with translation fidelity in yeast [20,21]. The above constructs allow us to assess the extent to which the rate of elongation affects the accuracy (fidelity) of mRNA translation, and explore what factors affect this.…”
Section: The Speed Of Translation Elongation Dictates Translation Accmentioning
confidence: 99%
“…In yeast, bacterial [19], and mammalian [9] cells, faster elongation rates compromise the accuracy of codon:anticodon recognition, although it has recently been reported that rates of translation elongation do not correlate with translation fidelity in yeast [20,21]. The above constructs allow us to assess the extent to which the rate of elongation affects the accuracy (fidelity) of mRNA translation, and explore what factors affect this.…”
Section: The Speed Of Translation Elongation Dictates Translation Accmentioning
confidence: 99%
“…More generally, high global (rather than proteinspecific) mistranslation rates could confer a selective advantage by generating a "statistical proteome"-a bet-hedging strategy whereby a few cells with some mistranslated proteins (rather than all cells with one specific mistranslated protein as in the previous example) can survive an environmental stress [15,16]. Such a mixed proteome can occur both as a consequence of baseline mistranslation (as shown by proteome analyses [1]) or through artificial or stress-induced mistranslation. One example of general, stress-induced proteome-wide beneficial mistranslation comes from work on mis-methionylation in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of protein mistranslation is amongst the highest known error rates in cellular biosynthetic processes, ranging from 1 in 10,000 to 1 in 100 mis-incorporated amino acids in E.coli [1,2]. As a result, 10 to 15% of all proteins in an actively growing E.coli cell are likely to carry at least one mis-incorporated amino acid [3,4], implying a high tolerance for mistakes.…”
Section: Introductionmentioning
confidence: 99%
“…A higher throughput means of detecting error rates is therefore highly desirable. A recent preprint has suggested a possible mass spectrometry-based approach [74], by exploiting the Maxquant software's [75] ability to perform a blind peptide modification search. While the sensitivity of the approach may limit it to study of the more abundant mis-translation error products, the authors data included altered error rates following perturbations such as amino acid starvation and the addition of an antibiotic known to effect ribosomal proofreading function, suggesting the method holds promise as a high-throughput means of investigating ribosomal error rates.…”
Section: Identifying Ribosome Heterogeneitymentioning
confidence: 99%